Методика выбора оптимальной конфигурации системы защиты информации - Серков, А. А.; Певнев, В. Я.; Нестеренко, Л. Ю. (НТУ "ХПИ", 2009)
Розглянуто критерії ефективності систем захисту інформації. Наведено етапи побудови систем технічного захисту інформації. Описано основні способи підвищення надійності технічних систем. Сформульована математична постановка задачі обрання конфігурації системи. Запропонована методика побудови системи захисту інформації, яка задовольняє завданим вимогам щодо надійності із урахуванням завданих обмежень.

The criteria of efficiency of the systems of protection to information are considered. The stages of the building of the systems of technical protection to information are presented. They ways of increasing to reliability of the technical systems are shown. Mathematical statement of the problem configuring systems is worded. The methods of the building of the system of protection to information, satisfying given requirements on reliability with provision for brought forth restrictions are offered.
Keywords: заданный уровень безопасности системы; ограниченный доступ; угрозы; целостность